The Marketing of Higher Education: Managing Student Loyalty Based on Tuition Fee Policy and Service Quality - Yunia Wardi; Abror Abror; Okki Trinanda (Jurnal Bisnis Manajemen, 2018)
This research investigates the influence of Single Tuition Fee System (STS) and Service Quality on Universitas Negeri Padang’s students’ intention to transfer to other universities. It also examines the correlation between Service Quality and STS in influencing the students’ intention to switch. The population of this study was 8,314 non-Bidikmisi Scholarship students from the class of 2013 and 2014. The sample size was determined by using Slovin formula, and it employed 400 students as the samples by using accidental sampling method. The data have been collected by using survey method with the questionnaires as the data collection method. This study analyzes the data by using path and correlation analysis. Before the main analysis, this study has conducted some preliminary analysis such as normality and multicollinearity test. The result of the research shows that: (1) the STS has a significant positive effect on students’ intention to transfer to other universities, (2) Service quality has a significant negative effect on students’ intention to transfer to other universities, and (3) There is a significant correlation between STS and service quality in influencing students’ intention to transfer to other universities. Some limitations and future study have been addressed.